Sifat Mekanis Kayu Salam Pada Kondisi Layan Basah - Kusumawardhani, Dina Tiara; Hidayatullah, Rizky; Bahtiar , Effendi Tri; Kapitan, Origenes Boy (Institut Teknologi Bandung, 2024)
Abstract The abundance of salam wood on the island of Java is an attraction for its use as a construction material. However, there is not much scientific information regarding the mechanical properties of salam wood. This study aims to identify some of the main mechanical properties of salam wood with destructive tests referring to ASTM D143 including tests for static bending, compression parallel to the grain, compression perpendicular to the grain, and shear, as well as physical properties of wood including density, specific gravity, and moisture content. Salam wood with small test samples free of defects in wet and air dry service conditions referring to SNI 7973:2013. The stress value generated in each test by air dry wood has a greater value than that of wet wood. In general, the wet service factor of the test results is not in accordance with the SNI value, but the static bending test for both MOE and MOR produces values that are close to the values required by SNI. Wet service conditions have a significant effect on the strength value of wood.